1998
DOI: 10.1007/s002709900305
|View full text |Cite
|
Sign up to set email alerts
|

Indications, management, and complications of temporary inferior vena cava filters

Abstract: Temporary filters are effective in trapping clots and protecting against PE, and the complication rate does not exceed that of permanent filters. They are an alternative when protection from PE is required temporarily, and should be considered in patients with a normal life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 23 publications
0
47
3
Order By: Relevance
“…Some investigators have reported the incidence of PTE during tIVCF placement as being between 0% 14,15) and ~ 4%. 16) Taking these reports and our results into consideration, tIVCF appears to have the ability to prevent PTE in patients with DVT.…”
Section: Discussionmentioning
confidence: 94%
“…Some investigators have reported the incidence of PTE during tIVCF placement as being between 0% 14,15) and ~ 4%. 16) Taking these reports and our results into consideration, tIVCF appears to have the ability to prevent PTE in patients with DVT.…”
Section: Discussionmentioning
confidence: 94%
“…Filter malposition or tilting is another important early complication that can reduce the effectiveness of the device to catch thrombi and predispose to recurrent PE (10). Other rare early complications include failure of the filter to open, vessel penetration, air embolism, and sheath kinking (11)(12)(13). Late complications are uncommon but include recurrent PE, caval thrombosis, filter migration, and filter fracture (1,3,14,15).…”
Section: Discussionmentioning
confidence: 97%
“…3,5,7,8 The frequency of fi lter thrombosis and IVC occlusion have been reported in 3.5% to 17.5% of patients. 5 The hypercoagulation state in the malignant disease has been reported to be a predisposing factor for caval occlusion within the fi rst year after fi lter placement. 9,10 In our case, lower extremity venous thrombosis developed and occluded the t-IVC-f in spite of the anticoagulation therapy or thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Such cases include the following: (1) acute PTE during anticoagulation therapy; (2) PTE or DVT with transient contraindications against anticoagulant therapy; (3) prophylactic fi lter insertion in patients with DVT or PTE to prevent PTE during thrombectomy or thrombolytic therapy. [3][4][5][6] Temporary-IVC-f complications such as fi lter dislocation, inferior vena cava (IVC) perforation, fi lter thrombosis, and IVC occlusion have also been reported. 3,5,7,8 The frequency of fi lter thrombosis and IVC occlusion have been reported in 3.5% to 17.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation